Glioma-Associated Oncogene Homolog1 (Gli1)-Aquaporin1 pathway promotes glioma cell metastasis - Liao, Zheng-qiang (BMB Rep, 2016)
Glioma-Associated Oncogene Homolog1 (Gli1) is known to be activated in malignant glioma; however, its downstream pathway has not been fully explained. The aim of this study was to explore the role of Gli1-Aquaporin1 (AQP1) signal pathway in glioma cell survival. Our data suggests that both Gli1 and AQP1 are upregulated in glioma tissues, as in comparison to in normal tissues. These up-regulation phenomena were also observed in glioma U251 and U87 cells. It was demonstrated that Gli1 positively regulated the AQP1 expression. By luciferase reporter gene and ChIP assay, we observed that this modulation process was realized by combination of Gli1 with AQP1 promotor. In addition, knock down of Gli1 by siRNA interference reduced the viability of glioma cells as well as suppressed cell metastasis. Also, the inhibitory effects of cell survival by silenced Gli1 were abrogated by AQP1 overexpression. In summary, glioma cell survival is a regulatory process and can be mediated by Gli1-AQP1 pathway. [BMB Reports 2016; 49(7): 394-399]